FACTORS ASSOCIATED WITH NURSES' COMPLIANCE IN DOCUMENTING NURSING CARE IN ELECTRONIC MEDICAL RECORDS AT RSUD PAMEUNGPEUK GARUT - Iman Nurjaman; Daryana; Ina Saparlina (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the relationship between nurse characteristics and factors associated with nurses’ compliance in documenting nursing care in EMRs at RSUD Pameungpeuk Garut. This research employed an analytic survey with a cross-sectional approach and involved 94 respondents. Primary data were collected using questionnaires on nurses’ characteristics, knowledge, attitude, motivation, and head nurse supervision. Data analysis was conducted using the Chi-Square test. The results showed a significant relationship between head nurse supervision (p = 0.027) and nurses' compliance in documenting nursing care in EMRs. The study concludes that there is a relationship between head nurse supervision and nurses’ compliance in nursing care documentation within EMRs. Nurses who receive regular supervision tend to have higher compliance in documentation compared to those who are not supervised by the head nurse.